STRATEGI KOMUNIKASI QUR’ANI SEBAGAI MODAL SOSIAL DAKWAH: PENDEKATAN BALĀGHAH-PRAGMATIK UNTUK PENGEMBANGAN LITERASI KEAGAMAAN MASYARAKAT - Rini angraini; Putri Sawaliyah Sitorus; Nurpadila; Nabila Putri Febrian; Fauziah Nur Ariza; Nurul Natasya Nabilah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article presents an interdisciplinary approach based on balāghah and pragmatics in understanding the Qur'anic dialogue as a strategy for developing religious communication in society. By analyzing more than 60 dialogic verses through the theory of speech acts (Searle) and implicature (Grice), it is found that dialogue in the Qur'an has transformational power in forming religious awareness, social ethics, and spiritual reflection. The integration of classical rhetorical devices and modern communicative functions offers a new conceptual framework in developing community-based religious literacy. The results of this study are proposed as a basis for designing inclusive and communicative strategies for preaching, education, and strengthening religious identity in contemporary Muslim society. Keywords: balāghah; pragmatics; da'wah; community development; Qur'anic communication